Effect of Tronclass combined with team-based learning on nursing students’ self-directed learning and academic performance: a pretest-posttest study - Longyi Hu; Siqi Li; Leshan Zhou (BMC Medical Education)
Abstract Background Self-directed learning ability is crucial for lifelong learning. The inadequate self-directed learning ability of nursing students in China may be due to their deficiency in self-management or learning initiative. Objective To explore the effect of online learning platform (Tronclass) combined with team-based learning on nursing students’ self-directed learning and academic performance. Design Pretest-posttest design. Participants From March to July 2023, 69 undergraduate third-year nursing students from a university in Hunan Province were selected through a whole-group sampling method. Methods This study used Tronclass to carry out team-based learning in the teaching process of pediatric nursing courses. It compared the self-directed learning ability nursing students before and after courses, and juxtaposed their academic performance with those of their counterparts who graduated in previous years. Results When comparing compare motivation, self-management, teamwork and information literacy, which are four subscale aspects of the self-directed Learning Ability Scale, the post-survey scores for these four dimensions are greater than the pre-survey results. The results of the study showed a statistically significant difference (P < 0.05), in the students who engaged in Tronclass combined with team-based learning. Specifically, these students received higher midterm and final grades than to those who had already graduated and did not participate in these activities. (P < 0.05). Conclusion Combining Tronclass with team-based learning enhances nursing students’ ability to engage in self-directed learning and improves their performance in midterms and finals, thereby fostering the development of comprehensive competence.